Die Sprachstil Im Artikel In Der Deutschland Magazin Im April/ Mai 2010 - MAGDALENA ANALINDA DASAN, MARIA (LATERNE, 2013)
As a communication, language produce a shape that called text. Article is one of written text. In understanding a text, while oral text although written text, language has important act. the meaning. The statement of the problem are the style of language that usually the autor using in written deutschland magazine and the kinds of style of language that usually the author using in written Deutschland magazine. The objectivities of the problem are to know the language style have been in the article of deutschland magazine and to know the kinds of style of language that usually the author using in written deutschland magazine. This research using qualitative descriptive are display data about the words and sentence finds in the articles of Deutschland magazine. The data analyse by the style of language. The result of the research shows the language style using in the article are of language hyperbola, allusion, zeugma, figurative, anticipate, anticlimax katabasis, paralelisme, climax. The most of style of language is symbolic that contained compare of language. The author hopes this thesis has benefit for the reader. So can support of the study especially deutsch. Keywords: article in Deutschland magazine, the style of language